2008
DOI: 10.1007/s11270-008-9652-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aeration Rate on Nutrient Removal from Slaughterhouse Wastewater in Intermittently Aerated Sequencing Batch Reactors

Abstract: The effect of aeration rate on nutrient removal from slaughterhouse wastewater was examined in two 10-L laboratory-scale sequencing batch reactors (SBRs-SBR1 and SBR2) operated at ambient temperature. The contaminants in the slaughterhouse wastewater had average concentrations of 4,000 mg chemical oxygen demand (COD) L −1 , 350 mg total nitrogen (TN) L −1 and 26 mg total phosphorus (TP) L −1 . The duration of a complete SBR operation cycle was 8 h and comprised four operational phases: fill (7 min), react (393… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 24 publications
(27 reference statements)
3
27
0
3
Order By: Relevance
“…This indicates end of nitrification. If aeration would be terminated before the sharp increase, the energy input would be saved [15]. In addition, since the AOR:NOR ratios at DO of 4 mg/L were higher than those at DO of 1.2 mg/L, maintaining the operation of the IASBR reactors at lower DO levels would benefit partial nitrification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates end of nitrification. If aeration would be terminated before the sharp increase, the energy input would be saved [15]. In addition, since the AOR:NOR ratios at DO of 4 mg/L were higher than those at DO of 1.2 mg/L, maintaining the operation of the IASBR reactors at lower DO levels would benefit partial nitrification.…”
Section: Resultsmentioning
confidence: 99%
“…Efficient partial nitrification has been observed in intermittently aerated sequencing batch reactors (IASBRs) treating wastewater [13,14]. It is reported that IASBRs treating slaughterhouse wastewater achieved a NO 2 --N level of up to 96% of the total oxidized nitrogen (TON, NO 2 --N and NO 3 --N), in addition to COD and total nitrogen (TN) removals from wastewater of more than 94 and 92%, respectively [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Los parámetros medidos a la entrada, salida de cada una de las fases de la etapa de reacción y al finalizar el tratamiento de cada ciclo fueron los siguientes: pH (4500-B), DBO [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] (SM 5210), DQO T y DQO S (5220-C), NTK (4500-Norg-B), N-NH 4 + (4500-NH 3 -B), N-NO 2 -(4500-NO2 2 --B), N-NO 3 -(4500-NO 3 --D), NT (4500-Norg-B), PT (4500-P-C), P-PO 4 -3 (4500-P-C), alcalinidad total (2320 B), SS (2540-F), SSV (2540-E) y SST (2540-D) según los procedimientos establecidos en el Método Estándar [15]. Para la determinación de la DQO S , las muestras fueron previamente filtradas por una membrana de celulosa y un tamaño de poro de 0,45 µm (Whatman).…”
Section: Materiales Y Métodosunclassified
“…Es por esto que en la actualidad se ha visto la necesidad de remover simultáneamente la materia orgánica, el nitrógeno y el fósforo en los efluentes provenientes de los mataderos de reses, realizándose exitosamente mediante la aplicación de tratamientos biológicos con sistemas no convencionales de lodos activados, como los reactores por carga secuencial (SBR) [7][8][9][10].…”
Section: Introductionunclassified
“…Li et al [10] found that, at an aeration rate of 0.8 l air/ min, after the depletion of ammonium-N (NH 4 ? -N), DO in the reactor during the aeration periods reached 70% of DO saturation.…”
Section: Introductionmentioning
confidence: 99%